Analisis Perbandingan Efektifitas Iklan Cetak dan Iklan Digital dalam Meningkatkan Penjualan Produk di Toko Istana Sarung Wonorejo - Wahidatun Nikmah; Aprilia Wulandari; Nufaila Putri; Achmad Candra Irawan; Abdurrohim Abdurrohim; Miftahul Huda (Jurnal Manajemen Bisnis Era Digital, 2025)
This study aims to compare the effectiveness of print and digital advertisements in increasing sarong sales at Toko Istana Sarung Wonorejo. Using a quantitative approach, sales data from the first three months of 2025 were analyzed based on digital advertisements (social media), print advertisements (brochures and banners), and word-of-mouth promotions. The results show that digital advertising had the greatest impact on sales growth (approximately 50%), followed by word-of-mouth promotion (5–10%), and print advertising (around 15%). These findings highlight the importance of a multichannel marketing strategy tailored to consumer characteristics.